2022
DOI: 10.1038/s41598-022-10263-3
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of excess depressive disorder in women and men living with HIV in France compared to the general population

Abstract: We aimed to estimate the prevalence of depressive disorder in people living with HIV (PLWH) and evaluate its association with non-HIV-specific and HIV-specific factors in PLWH and in PLWH compared to the general population (GP). We used cross-sectional data from the QuAliV study, conducted within the ANRS-CO3 Aquitaine-AQUIVIH-NA cohort of PLWH in Nouvelle-Aquitaine (2018–2020), and a nationally-representative survey in the GP (EHIS-ESPS, 2014–2015), we included all participants aged ≥ 18 years old who had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
1
3
1
Order By: Relevance
“…This finding is consistent with previous research, showing HIV-related stigma to be strongly associated with poorer HRQoL, specifically in the psychological and social QoL 26 , 27 . Similar patterns have been observed in research on depressive syndrome in PLWH compared to those in the general population, wherein we observed a dose–response relationship between the prevalence of depressive syndrome and level of HIV-related stigma 28 . Different forms of HIV-related stigma, which are potentially compounded by intersectional stigma faced by populations disproportionately affected by HIV (e.g.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with previous research, showing HIV-related stigma to be strongly associated with poorer HRQoL, specifically in the psychological and social QoL 26 , 27 . Similar patterns have been observed in research on depressive syndrome in PLWH compared to those in the general population, wherein we observed a dose–response relationship between the prevalence of depressive syndrome and level of HIV-related stigma 28 . Different forms of HIV-related stigma, which are potentially compounded by intersectional stigma faced by populations disproportionately affected by HIV (e.g.…”
Section: Discussionsupporting
confidence: 87%
“…It has previously been shown that PLWH are more likely to suffer from mental health disorders than the general population [10,[12][13][14]. In this study, the burden of MDE and PTSD among PLWH was higher than in the Rwandan general population, but the difference was statistically non-significant.…”
Section: The Burden Of Mental Health Disorders Among Plwhcontrasting
confidence: 69%
“…Mental health disorders are among the NCDs which pose a substantial burden of disease for this population [7][8][9][10]. According to a recent systematic review, up to 62% of PLWH experience mental health symptoms [10], and particularly depression is common among PLWH with prevalence rates up to 4 times higher than in the general population [10][11][12][13][14]. In addition to the burden of disease, comorbidity of mental health disorders among PLWH can complicate medication adherence [15][16][17], jeopardize viral suppression [18,19], and increase the risk of clinical HIV progression [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the injection of interferon- γ and poly(I:C), a Toll-like receptor-3 (TLR3) agonist mimicking the effect of HCV double-strand RNA, caused depression-like symptoms, and the proinflammatory genes were synergistically induced in the hippocampus and prefrontal cortex [ 105 ]. The tight association between HCV infection and depression suggests that optimal care for the overall well-being of patients with HCV infection needs adequate knowledge of their psychological status [ 114 ]. Infection with human immunodeficiency virus (HIV) has been associated with an increase in the prevalence of depression [ 115 , 116 ].…”
Section: Microglia and Psdmentioning
confidence: 99%